Research progress of probiotics intervention on reconstruction of intestinal flora and improvement of quality of life in patients after endometrial cancer surgery - Chen, Wei; Chen, Xiao; Fang, Yi; Sun, Yang; Lin, Yibin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aims to comprehensively assess the impact of probiotic supplementation on gut microbiota composition and quality of life in endometrial cancer (EC) patients, offering clinical insights supported by empirical data.MethodsA systematic search was conducted across multiple databases, including PubMed, EMBASE, Cochrane Library, Web of Science, and CNKI, covering literature up to mid-2023. Only randomized controlled trials (RCTs) investigating probiotic administration in EC surgery patients were selected. Key evaluation metrics encompassed gut microbial diversity indices, shifts in specific bacterial populations, quality of life assessments, gastrointestinal symptom severity, and immune response indicators. Statistical analyses were performed using RevMan 5.4 and Stata 16.0 software.ResultsThe meta-analysis incorporated 18 RCTs with a total of 1,246 participants. Findings revealed that probiotic supplementation significantly enhanced α-diversity (SMD = 0.68, 95% CI: 0.41–0.95, p < 0.001) and increased the prevalence of beneficial microbes, including Bifidobacterium (SMD = 1.12, 95% CI: 0.78–1.46, p < 0.001) and Lactobacillus (SMD = 0.93, 95% CI: 0.65–1.21, p < 0.001). Conversely, opportunistic pathogens like Bacteroidetes exhibited reduced abundance (SMD = -0.54, 95% CI: -0.82 to -0.26, p < 0.001). Clinically, probiotic use led to notable improvements in overall quality of life (MD = 8.74, 95% CI: 5.12–12.36, p < 0.001) and alleviated gastrointestinal disturbances, such as diarrhea (RR = 0.45, 95% CI: 0.32–0.63, p < 0.001) and constipation (RR = 0.57, 95% CI: 0.42–0.78, p < 0.001). Additionally, inflammatory markers, including IL-6 (SMD = -0.76, 95% CI: -1.05 to -0.47, p < 0.001) and TNF-α (SMD = -0.64, 95% CI: -0.93 to -0.35, p < 0.001), were significantly lowered. Subgroup analyses indicated superior efficacy with multi-strain formulations, higher dosages (≥1010 CFU/day), and extended treatment durations (≥8 weeks).ConclusionCurrent evidence supports the beneficial role of probiotics in restoring gut microbiota balance, enhancing patient well-being, mitigating digestive complications, and reducing systemic inflammation following EC surgery. Further high-quality research is warranted to refine optimal probiotic strains, dosing strategies, and intervention timing.